Em busca de justiça climática: a atuação da sociedade civil na COP27 para a agenda de perdas e danos - Martins, Kaio Anderson Vieira (2024)
This work seeks to analyze the mechanisms employed by civil society at COP27 regarding the agenda of loss and damage. The conference represented a historic milestone in climate negotiations, with the approval of the Loss and Damage Fund and a greater recognition of the importance of this issue. After more than three decades of advocating for compensation for the effects of climate change, developing countries, led by the most vulnerable states and endorsed by international civil society, secured a commitment from developed nations to create an emergency financing mechanism for the impacts of climate change. Using a case study approach, based on conceptual-analytical review, this research investigates the participation of international civil society at COP27, focusing on its role in shaping the loss and damage agenda during fund negotiations. The study observes the use of mechanisms such as information dissemination, networking, normative embedding, and demand for justification by civil society to influence decisions made at the conference. The research is structured into periods covering the history of loss and damage before and during COP27, with a primary focus on civil society's actions. The findings trace the trajectory of civil society's engagement at the conference in contrast to the identified mechanisms.